Surgical care in district hospitals in sub-Saharan Africa: a scoping review - Bentounsi, Z; Sheik Ali, S; Drury, GJ; Lavy, C (BMJ Publishing Group, 2021)
Objective To provide a general overview of the reported current surgical capacity and delivery in order to advance current knowledge and suggest targets for further development and research within the region of sub-Saharan Africa.